2018
DOI: 10.31276/vjste.60(3).33
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterisation of a soybean galactinol synthase gene under various stress conditions

Abstract: Galactinol synthase (GolS) has been known to play a key role in raffinose biosynthesis by catalysing the formation of galactinol. The GolS gene family has been recently identified in various plant species. Among them, many individual GolS genes have been reported to function in plant stress tolerance. In this study, we reported the construction of transgenic Arabidopsis overexpressing a soybean GolS gene, GolS2. There were no significant differences in the phenotypes of the transgenic and control plants during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…GolS genes have already been surveyed in other species, such as A. thaliana (TAJI et al, 2002), Salvia miltiorrhiza (WANG et al, 2012), C. arabica and C. canephora (DOS SANTOS et al, 2011;, Camellia sinensis (ZHOU et al, 2017), Malus × domestica (FALAVIGNA et al, 2018), Sesamum indicum L. (YOU et al, 2018) and Glycine max (CHU et al, 2018). In this study, we performed an in silico analysis of the four GolS genes identified in the M. acuminata genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GolS genes have already been surveyed in other species, such as A. thaliana (TAJI et al, 2002), Salvia miltiorrhiza (WANG et al, 2012), C. arabica and C. canephora (DOS SANTOS et al, 2011;, Camellia sinensis (ZHOU et al, 2017), Malus × domestica (FALAVIGNA et al, 2018), Sesamum indicum L. (YOU et al, 2018) and Glycine max (CHU et al, 2018). In this study, we performed an in silico analysis of the four GolS genes identified in the M. acuminata genome.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, with the growing availability of information generated by genome sequencing in plants, many studies have been conducted for identifying and understanding the functional significance of inumerous genes. GolS genes have been the subject of several studies in many plant species, and are genes that are upregulated in reponse to multiple developmental and environmental responses (DOS SANTOS et al, 2015;KANNAN et al, 2016;LIU et al, 2016;JANG et al, 2018;CHU et al, 2018). In an effort to accelerate the genomic studies in banana, a double haploid (DH-Pahang) had its genome sequenced, and a platform was made available for the characterization of its genes (D'HONT et al, 2012;DROC et al, 2013).…”
Section: Introductionmentioning
confidence: 99%